2017
DOI: 10.1080/10715762.2017.1327714
|View full text |Cite
|
Sign up to set email alerts
|

Sodium meta-arsenite induced reactive oxygen species in human red blood cells: impaired antioxidant and membrane redox systems, haemoglobin oxidation, and morphological changes

Abstract: Arsenic (As) is an air and water toxicant that causes cancer in multiple organs. Humans are exposed to As through contaminated water. We have examined the cytotoxicity of sodium meta-arsenite (SA), an As(III) compound, in human red blood cells (RBC) under in vitro conditions. Haemolysates were prepared from human RBC treated with different concentrations of SA (0.1-5.0 mM) for 5 h at 37 °C. SA treatment of RBC caused significant increase in methaemoglobin formation, protein and lipid oxidation, and nitric oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…SA‐induced oxidative stress damages heme proteins, mainly Hb due to its abundance in RBC, which releases the bound iron . Heme proteins were protected from this damage by DHB in a dose dependent manner since concentration of free iron in hemolysates was decreased in the DHB + SA samples, compared to SA alone treated RBC (Figure ).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…SA‐induced oxidative stress damages heme proteins, mainly Hb due to its abundance in RBC, which releases the bound iron . Heme proteins were protected from this damage by DHB in a dose dependent manner since concentration of free iron in hemolysates was decreased in the DHB + SA samples, compared to SA alone treated RBC (Figure ).…”
Section: Resultsmentioning
confidence: 95%
“…Human RBC were incubated with 0.5–5.0 mM DHB at 37°C for 30 min followed by treatment with 2.5 mM SA for 5 h at 37°C. The dose of SA used (2.5 mM) was based on our previous results . SA at 2.5 mM concentration produces significant changes in parameters to be determined so that protective effect of DHB could be evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CD spectrum of HHb shows two characteristic minima at 208 and 222 nm, reflecting the α-helical structure of the HHb. [37][38][39] Figure 8 shows that the secondary structure of HHb has not experienced substantial structural changes after the addition of different concentrations of CNP. This data indicated that the regular secondary structure of the HHb remained unchanged after interaction with CNP.…”
Section: Studiesmentioning
confidence: 99%
“…Arsenite causes extensive damage to red blood cells, which impairs their antioxidant system and alters the major cellular metabolic pathways (Maheshwari, Khan, & Mahmood, 2017). Splenomegaly with hypersplenism may be present in association with arsenic-related liver disease (Nevens et al, 1990).…”
Section: Hematologic Disordersmentioning
confidence: 99%